Voice over IP signaling H.323 and beyond. - Liu, Hong (IEEE Communications magazine)
Signaling has been one of the key areas of Voice over IP (VoIP) technologies since inception. H.323 was the key protocol that allowed interoperability of VoIP products and moved the industry away from the initial proprietary solutions. Once the VoIP industry started maturing, some limitations of H.323 came to light. In this article we provide an overview of H.323, describe its capabilities, and discuss how its limitations are being addressed using the concept of gateway decomposition. We also discuss how H.323 can coexist with other protocols such as MGCP, H.248, and SIP which are attracting a lot of interest in the VoIP industry today